2009
DOI: 10.1002/sce.20353
|View full text |Cite
|
Sign up to set email alerts
|

The role of induction in learning to teach toward equity: A study of beginning science and mathematics teachers

Abstract: ABSTRACT:We investigated how an induction program supported and constrained beginning teachers' efforts to teach science or mathematics in equitable and effective ways. We focused our investigation on the teaching and learning of equitable instructional practices; we conceived of such practices as attention to students' experiences, instruction for English learners, differentiation, and reform-minded science or mathematics strategies. During the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 47 publications
1
49
0
2
Order By: Relevance
“…Differentiated instruction allows teachers to provide choices to the students concerning content, learning processes, and products by, for example, using varied resource materials, tasks, and texts or adapting curriculum to students' learning processes [68]. Specifying these general characteristics of differentiated instruction, the two extreme subtypes as well as the mixed subtypes found in the present study indicate that mathematics teachers should differentiate content, learning processes, and products by considering students' different levels of perceived structuredness, support, and discursive effectiveness.…”
Section: Implications For Educational Practicementioning
confidence: 99%
“…Differentiated instruction allows teachers to provide choices to the students concerning content, learning processes, and products by, for example, using varied resource materials, tasks, and texts or adapting curriculum to students' learning processes [68]. Specifying these general characteristics of differentiated instruction, the two extreme subtypes as well as the mixed subtypes found in the present study indicate that mathematics teachers should differentiate content, learning processes, and products by considering students' different levels of perceived structuredness, support, and discursive effectiveness.…”
Section: Implications For Educational Practicementioning
confidence: 99%
“…Although a seemingly straightforward recommendation, listening to students' interests, experiences and ideas is challenging for teachers to do. In my own study of two beginning teachers learning to teach toward equity and diversity (Bianchini and Brenner 2010), I found attending to students' experiences and interests the weakest dimension of equitable practices implemented. Kristen, a beginning high school mathematics teacher, for example, identified starting instruction from students' lives as an important instructional goal; however, she rarely integrated students' experiences into her lessons.…”
Section: The Individual and The Group In Learning Sciencementioning
confidence: 98%
“…In contrast, Long (2010) suggests the key to a successful process of matching beginning teachers to suitable coaches is based on similar professional content areas, learning styles, age, gender and culture, as well as personality variables. Bianchini and Benner (2009) concluded that having a coach in the same field is essential for deep knowledge to be shared and developed. In a five-year longitudinal study started in the [2007][2008] school year, conducted by Gray and Taie (2015), the percentage of beginning teachers who were currently teaching in each subsequent year was larger among those who were assigned a first-year mentor than among those not assigned a first year mentor.…”
Section: Induction Coachingmentioning
confidence: 99%
“…In the middle of his story, Henry is finally placed with an induction coach who happens to be a Special Education Teacher. His hesitation about this pairing is clearly apparent, and he wonders how she will be able to support him in an automotive class (Bianchini & Benner, 2009). …”
Section: Big Narrative #1: Henry's Story Of Self-identitymentioning
confidence: 99%
See 1 more Smart Citation